Kelp holobiont responses to run-off in Billefjorden, Svalbard in August 2022 - Sarina Niedzwiedz; Claudia Elena Schmidt; Yunlan Yang; Bertille Burgunter-Delamare; Sebastian Andersen; Lars Hildebrandt; Daniel Pröfrock; Helmuth Thomas; Rui Zhang; Børge Damsgård; Kai Bischof (PANGAEA, 2024)
Kelps act as ecosystem engineers and foundation species, providing the food web basis for Arctic coastal, rocky shore ecosystems. Arctic fjords are undergoing large climatic changes, with the consequences of glacial and terrestrial run-off on kelp holobionts largely being unknown. We compared areas being influenced by either glacial or terrestrial run-off with a control area in Billefjorden, Svalbard in August 2022. Kelps were collected from three sampling stations (A-I) per area, with a plant rake (Plant rake 19.000, acc. to Sigurd Olsen, KC Denmark, Silkeborg, Denmark) on 5±2 m water depth. Silica-dried meristematic tissue was used for biochemical (pigment, antioxidant activity) analyses. The tissue above the meristem was rinsed with ultrapure water and freeze-dried, before elements were measured of homogenized, digested material with a triple quadrupole ICP-MS/MS system (Agilent 8800, Agilent Technologies; Tokyo, Japan). For microbial analyses, an area of 10 exttimes10 cm above the meristem was swabbed with a sterile cotton swab. The V4-V5 regions (515F: 5 extquotesingle-GTGCCAGCMGCCGCGGTAA-3 extquotesingle and 907R: 5 extquotesingle-CCGTCAATTCMTTTRAGTTT-3 extquotesingle) of the bacterial 16S rRNA gene from DNA extracts were amplified and sequenced using the Illumina Nova platform (Shanghai Hanyu Biotech lab, Shanghai, China).